2023
DOI: 10.1111/jvh.13897
|View full text |Cite
|
Sign up to set email alerts
|

Excellent hepatitis C virus cure rates despite increasing complexity of people who use drugs: Integrated‐Test‐stage Treat study final outcomes

Margaret O'Sullivan,
Anna‐Marie Jones,
Adele Mourad
et al.

Abstract: Achieving hepatitic C virus (HCV) elimination requires linking people who use drugs (PWUD) into care. We report final direct‐acting antivirals (DAAs)‐based outcomes from the Integrated‐Test‐stage ‐Treat (ITTREAT) study. Project ITTREAT (2013–2021), based at an addiction centre, was a ‘one‐stop’ service with innovative linkage to care strategies. Primary outcome was sustained virological response (SVR12) (intention to treat ITT) including whether individuals were recruited in first (period 1) versus last four (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In another UK study of 270 PWID who received HCV treatment at an addiction center observed 41 deaths (15%) during the 8-year study period; drug overdose was the most common cause of death among those whose cause of death could be ascertained. [16] In a third Canadian study of people living with HIV in clinical care, mortality was three times higher in individuals who experienced HCV reinfection after initial SVR. [14] These data underscore the importance of addressing non-liver outcomes and the syndemic of opioid use and viral infections in patients at high risk of HCV reinfection.…”
Section: Outcomes Of Hcv Reinfection In Pwidmentioning
confidence: 99%
See 2 more Smart Citations
“…In another UK study of 270 PWID who received HCV treatment at an addiction center observed 41 deaths (15%) during the 8-year study period; drug overdose was the most common cause of death among those whose cause of death could be ascertained. [16] In a third Canadian study of people living with HIV in clinical care, mortality was three times higher in individuals who experienced HCV reinfection after initial SVR. [14] These data underscore the importance of addressing non-liver outcomes and the syndemic of opioid use and viral infections in patients at high risk of HCV reinfection.…”
Section: Outcomes Of Hcv Reinfection In Pwidmentioning
confidence: 99%
“…[10] Several additional studies have since been published, with reinfection rates ranging from 1.8/100 PY (95% CI: 0.6-5.6) in a UK cohort treated at an addiction center to 28.7/100 PY (95% CI: 16.3-50.6) among persons in an Australian prison who reported recent IDU and sharing of needles/syringes (Table 1). [11][12][13][14][15][16][17][18][19][20] In addition to IDU, factors associated with higher rates of reinfection include younger age, experiencing unstable housing or homelessness, receipt of HCV treatment while in prison, and recent needle or syringe sharing. [11,13,15,19] Notably, much of this research has been conducted outside of the United States.…”
Section: Incidence Of Hcv Reinfection In Pwidsmentioning
confidence: 99%
See 1 more Smart Citation